Multimodal imaging of soccer ball-related ocular posterior segment injuries. Issue 6 (November 2022) - Carrera, William; Ng, Caleb; Koppinger, Jayson; Saud, Asma; Chen, Judy J; Agarwal, Anita; Johnson, Robert N; Jumper, J. Michael; Lujan, Brandon; McDonald, H. Richard
Purpose: To investigate the clinical and anatomic characteristics of soccer ball-induced posterior segment injuries in the era of modern multi-modal imaging. Methods: Retrospective case series of patients with soccer ball injury and diagnostic imaging from 2007 to 2020 at a single vitreoretinal practice. Results: Eight patients met inclusion criteria. Fundus photographs (FP) and optical coherence tomography (OCT) were obtained in eight patients, fundus autofluorescence (FAF) in five patients, fluorescein angiography (FA) in three patients, and en-face OCT and OCT-Angiography (OCT-A) were obtained in two patients each. FA and FAF identified traumatic pigment epitheliopathy secondary to commotio. Increased hypo-autofluorescence was associated with shallow, peripheral retinal detachment on FAF. OCT of the macula displayed outer retinal changes associated with commotio, and offered insight into the acute and subacute changes of traumatic macular hole formation. A patient displayed foveal hyper-reflectivity in the shape of an hourglass with retinal cyst at the level of the external limiting membrane (ELM) as seen on OCT and En-face OCT. A patient with commotio involving the macula lacked microvascular changes on OCT-A. Conclusion: OCT, FA, and FAF imaging may aid in the work-up and management of the soccer ball-related posterior segment injuries.